Effect of Culture Filtrates of Tomato Plant Pathogenic Fungi on Seed Germination and Seedling Growth of Tomato (Lycopersicon esclentum Mill.) - Raithak, P. V.; Gachande, B. D. (Current Botany, 2013)
Pathogenic fungi, Fusarium oxysporum f.sp. lycopersici and Alternaria solani were isolated from infected tomato roots and fruits respectively from different varieties of tomato (Lycopersicon esclentum Mill.). The effect of culture filtrate of these fungi was observed on seed germination, root, and shoot length and vigour index. It was found that, culture filtrate obtained from F. oxysporum f. sp. lycopersici isolated from tomato varieties Laxmi (NP-5005) increased seed germination up to 80 % vigour index 904.0, root length 6.14 cm and shoot length 5.16 cm as compared to other varieties. Alternaria solani isolated from var. Priya (BSS-908) increased seed germination up to 70%, vigour Index 784.7, root length 5.93 cm and shoot length 5.28 cm as compared to other varieties.